Diagenetic evolution of a fractured evaporite deposit (Vilobí Gypsum Unit, Miocene, NE Spain). Issue 2 (9th February 2013) - Moragas, M.; Martínez, C.; Baqués, V.; Playà, E.; Travé, A.; Alías, G.; Cantarero, I.
Abstract The upper Burdigalian Vilobí Gypsum Unit, located in the Vallès Penedès half‐grabben (NE Spain), consists of a 60‐m thick succession of laminated‐to‐banded secondary and primary gypsum affected by Neogene extension in the western part of Mediterranean Sea. This Tertiary extensional event is recorded in the evaporitic unit as six fracture sets (faults and joints), which can be linked with basin‐scale deformation stages. All fractures are totally or partially infilled by four types of new gypsum precipitates showing a large variety of textures and microstructures. A structural and petrological study of the unit allows us to establish the following chronology of the fracture formation and infilling processes, from oldest to youngest: (i) S1 and S2 normal faults sets formation and precipitation of sigmoidal gypsum fibres; (ii) S3 joint set formation and growing of perpendicular fibres; (iii) S4 inverse fault development, infilled by oblique gypsum fibres and deformation of the previous fillings; and (iv) S5 and S6 joint formations and later dissolution processes, infilled by macrocrystalline gypsum cements. The fractures provided the pathway for fluid circulation in the Vilobí Unit. The oxygen, sulphur and strontium isotope compositions of the host rocks and the new precipitates in the fractures suggest clear convective recycling processes from the host‐sulphates to the fracture infillings, recorded by a general enrichment trend to heavier S–O isotopes, from the oldest precipitates (sigmoidal fibres) to the youngest (macrocrystalline cements) and to the preservation of the strontium signals in the infillings.